Theabrownin and Poria cocos Polysaccharide Improve Lipid Metabolism via Modulation of Bile Acid and Fatty Acid Metabolism - Wang, Jieyi; Zheng, Dan; Huang, Fengjie; Zhao, Aihua; Kuang, Junliang; Ren, Zhenxing; Chen, Tianlu; Lei, Jing; Lin, Jingchao; Wang, Xiaoning; Jia, Wei; Xie, Guoxiang; et al. (Frontiers in Pharmacology, 2022)
Nonalcoholic fatty liver disease (NAFLD) is prevalent worldwide, while no pharmaceutical treatment has been approved. Natural herbs are promising for their amelioration effect on lipid metabolism. Theabrownin (TB) and Poria cocos polysaccharide (PCP) have been reported to have effect on hyperlipidemia and diabetes. Here, we compared the effect of individual TB or PCP and the combination of TB and PCP (TB + PCP) on NAFLD phenotypes and the alteration of metabolism in the mice with high-fat diet. The results showed that TB, PCP, and TB + PCP reduced serum and hepatic lipid levels, among which TB + PCP was the most effective. Serum metabolomic profile and liver mRNA analyses revealed that the treatments altered metabolic pathways involved in fatty acid metabolism, bile acid metabolism, and tricarboxylic acid cycle, which was also most significant in the TB + PCP group. This study demonstrated that TB, PCP, especially the combination of TB and PCP could be potential therapeutic formula for NAFLD that promoted lipid utilization and inhibited lipid synthesis and absorption.